2012
DOI: 10.1364/ol.37.001529
|View full text |Cite
|
Sign up to set email alerts
|

High power supercontinuum generation in a nonlinear ytterbium-doped fiber amplifier

Abstract: High power supercontinuum generation with 70 W average output power in a nonlinear ytterbium-doped fiber amplifier is demonstrated using all-normal dispersion, all-fiber master oscillator power amplifier configuration. The supercontinuum covers from 1064 nm to beyond 1700 nm with spectral flatness better than 12 dB and 67.3% optical to optical conversion efficiency. The almost uniform spectral power density across the whole continuum is more than 70 mW/nm and the nanosecond bursts output have an effective peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 12 publications
5
48
0
Order By: Relevance
“…The data of the final output spectrums are averaged every 10 points in order to show the spectrums more clearly. The change of the width and the shape of the output spectrums with the increase of the small signal gain are in good agreement with the experiments in [9]- [10]. The results confirmed that for one thing, the Ginzburg-Landau equation and the noise model as well as the Raman response model used in this paper can accurately simulate near-infrared SC generation from a nonlinear fiber amplifier.…”
Section: Simulation Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The data of the final output spectrums are averaged every 10 points in order to show the spectrums more clearly. The change of the width and the shape of the output spectrums with the increase of the small signal gain are in good agreement with the experiments in [9]- [10]. The results confirmed that for one thing, the Ginzburg-Landau equation and the noise model as well as the Raman response model used in this paper can accurately simulate near-infrared SC generation from a nonlinear fiber amplifier.…”
Section: Simulation Resultssupporting
confidence: 87%
“…High power near-infrared SC has a wide variety of applications, such as remote chemical sensing [6], real time optical metrology [7], spectroscopy [8] to name a few. We have achieved 70W and 177.6W high power near-infrared SC in succession from a nonlinear fiber amplifier, which proved the advantages of nonlinear fiber amplifier in high power near-infrared SC generation [9]- [10].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, the obtained spectra did not meet the desired characteristics for CARS spectroscopy: in [10], the spectrum covered the visible region from 500 nm to 900 nm, i. e. out of the range of interest for the targeted application, and the spectrum reported in [11] suffered from deep undesirable modulations below the 1300 nm zero dispersion wavelength (ZDW), due to stimulated Raman scattering in normal dispersion regime. In 2012, Song et al reported the generation of a SC with a very high spectral power density (70mW/nm) over the range 1064-1700 nm [12]. This result was obtained at the expense of a very complicated setup involving multi-stage amplification, with both double clad and core-pumped Yb-doped PCFs.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, low repetition Q-switched or mode lock laser seed with high peak power is required [15], [16]. For the SC source with high average output power generated in fiber amplifier, the threshold pump power is very high reaching hundreds of Watts [17], [18].…”
mentioning
confidence: 99%